BE RESPONSIVE TO GET IN PRINT FASTER (Journal of Astronomy & Earth Sciences Education, 2017)
The vast majority of questions received by peer-reviewed journal editors revolve around one repeated and sometimes frantic theme: when will my article appear in print? Manuscript authors sometimes forget how many different procedural and sequential steps must occur before even the most scholarly and well-conceived “print-ready” article makes it into print. However, the most important steps where timelines seem to get unexpectedly extended are not actually those phases controlled by the publishers or the reviewers or the editors, but the critical steps related to the responsiveness of the authors themselves. The bottom line to helping publishers get scholarly work you can be proud of published in a timely matter is for authors to posture themselves in rapid response mode, replying promptly to correspondence from the journal.
Keywords: Publishing; Science Education